2016
DOI: 10.1021/acs.jpca.6b01402
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Acid-Catalyzed Dehydration of Cyclic Hemiacetals in Organic Aerosol Particles in Equilibrium with Nitric Acid Vapor

Abstract: Previous studies have shown that 1,4-hydroxycarbonyls, which are often major products of the atmospheric oxidation of hydrocarbons, can undergo acid-catalyzed cyclization and dehydration in aerosol particles to form highly reactive unsaturated dihydrofurans. In this study the kinetics of dehydration of cyclic hemiacetals, the rate-limiting step in this process, was investigated in a series of environmental chamber experiments in which secondary organic aerosol (SOA) containing cyclic hemiacetals was formed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…23 In contrast the − ONO 2 ligand is much more electron-poor (aqueous scale p K a of HNO 3 = −1.2). 24 The most electrophilic Ni III -oxygen adduct is therefore likely to be 3b , based on the E 0 Ni(II/III) for 3a .…”
Section: Resultsmentioning
confidence: 99%
“…23 In contrast the − ONO 2 ligand is much more electron-poor (aqueous scale p K a of HNO 3 = −1.2). 24 The most electrophilic Ni III -oxygen adduct is therefore likely to be 3b , based on the E 0 Ni(II/III) for 3a .…”
Section: Resultsmentioning
confidence: 99%
“…Significant OA loss due to heterogeneous oxidation can only be seen at photochemical ages as high as weeks . The enhancement of heterogeneous oxidation due to NO is remarkable only at OH concentrations close to the ambient values but not at typical values in an OFR (Richards-Henderson et al, 2015).…”
mentioning
confidence: 82%
“…6 are primary VOCs, except phenols and a dihydrofuran, which can be intermediates of the atmospheric oxidation of (alkyl)benzenes (Atkinson and Arey, 2003) and long-chain alkanes (Aimanant and Ziemann, 2013;Strollo and Ziemann, 2013;Ranney and Ziemann, 2016), respectively. Nevertheless, only the phenol production may occur in high-NO OFRs, as the particle-phase reaction in the photochemical formation of dihydrofurans from alkanes is too slow compared to typical OFR residence times (Ranney and Ziemann, 2016). Therefore, the impact of NO 3 oxidation on VOC fate needs to be considered only if the OFR input flow contains high NO mixed with biogenics and/or aromatics, e.g., (alkyl)benzenes and/or phenols.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…After 1,4-hydroxycarbonyls cyclize to form CHA they can undergo dehydration to form dihydrofurans, or oligomerization in which CHA undergo self-reactions to form acetals (Aimanant and Ziemann 2013b). Studies conducted on CHA in dry SOA in the presence of added HNO 3 showed that the dehydration of CHA is catalyzed by undissociated molecular HNO 3 (general acid catalysis) (Ranney and Ziemann 2016), whereas acetal formation is apparently catalyzed by H þ (specific acid catalysis) (Ziemann and Atkinson 2012). On the basis of these studies, CPHA is expected to undergo either dehydration or reaction with 1-propanol to form a peroxyacetal.…”
Section: Potential Reaction Pathways Of Ahpamentioning
confidence: 99%